Impact of Reproductive Trauma on Infertility Related Stress and Quality of Life - Das, Dipu (The Insight, 2023)
Background: Symptoms of psychological distress accompany both the infertility experience and its treatment. Objective:The purpose of this study is to assess the variations in infertility-related stress and quality of life (QoL) among women who are experiencing infertility and concurrent reproductive trauma. Concurrent reproductive trauma is defined as the loss of a pregnancy while experiencing infertility. Methodology and Materials:We interviewed 125 women who had infertility treatments at a tertiary hospital in Sylhet using a descriptive, cross-sectional study design. This allowed us to better understand their experiences. This study conducted in between January 2022 to May, 2022. Moreover, among 125 patients 100 patients belong to concurrent reproductive trauma group, n=100 whereas other 25 patients belong to infertility alone group.Participants filled out the Copenhagen Multi-center Psychosocial Infertility Fertility Problem Stress Scale (COMPI-FPSS), the Fertility Quality of Life instrument, and an additional infertility demographic questionnaire. Descriptive statistics, Pearson correlations, multivariate analysis of variance (MANOVA), univariate analysis of variance (ANOVA), and eta squared were employed in the statistical studies. Results: Simultaneous reproductive trauma was associated with considerably higher social stress (p<.001) and significantly poorer emotional QoL (p<.005) among participants than among women with infertility alone. Concurrent reproductive trauma was associated with greater levels of personal and marital stress, as well as poorer levels of mental, relational, and social QoL, although the difference was not statistically significant. Conclusion:During infertility therapy, women who have experienced reproductive trauma may benefit from psychiatric assistance to help them cope with the emotional sorrow of a previous miscarriage.